The impact of COVID-19 on antipsychotic prescriptions for patients with schizophrenia in Australia. (June 2022) - Kisely, Steve; Dangelo-Kemp, Dante; Taylor, Mark; Liu, Dennis; Graham, Simon; Hartmann, Jodie; Colman, Sam
Objective: To assess the impact, in the Australian setting, of the COVID-19 lockdown on antipsychotic supplies for patients with schizophrenia following a prescription from a new medical consultation when compared to the same periods in the previous 4 years. A secondary objective was to assess the volume of all antipsychotic supplies, from new and repeat prescriptions, over these same periods. Methods: A retrospective pharmaceutical claims database study was undertaken, using the Department of Human Services Pharmaceutical Benefits Scheme 10% sample. The study population included all adult patients with three or more supplies of oral or long-acting injectable antipsychotics for the treatment of schizophrenia at any time between 1 June 2015 and 31 May 2020. The primary outcome compared volumes of dispensed antipsychotics from new prescriptions (which require a medical consultation) between 1 April and 31 May each year from 2016 to 2020. This was to analyse the period during which the Australian Government imposed a lockdown due to COVID-19 (April to May 2020) when compared the same periods in previous years. Results: There was a small (5.7%) reduction in the number of antipsychotics dispensed from new prescriptions requiring a consultation, from 15, 244 to 14, 372, between April and May 2019 and the same period in 2020, respectively. However, this reduction was not statistically significant ( p = 0.75) after adjusting for treatment class, age, gender, location and provider type. Conclusion: The COVID-19 restrictions during April and May 2020 had no significant impact on the volume of antipsychotics dispensed from new prescriptions for patients with schizophrenia when compared to the volume of antipsychotics dispensed from new prescriptions during the same period in previous years.